2021
DOI: 10.1021/acsestengg.0c00253
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Emerging Wastewater Nutrient Removal and Recovery Technologies to Inform Practice and Advance Resource Efficiency

Abstract: Advancing nutrient recovery from idea to implementation requires reporting practices that facilitate comparison among diverse nutrient removal and recovery (NRR) technologies and enhance the translation of academic research to practice. We reviewed 157 technologies that treat nitrogen-and/or phosphorusladen wastewater across several underlying mechanisms, stages of development, and scales of operation. We outline a systematic reporting and analysis framework to characterize NRR technologies using quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 298 publications
0
63
0
Order By: Relevance
“…We expect the relative importance of the core metrics of sensitivity, deployability, selectivity, and energy consumption to vary across these sensing applications. Similar tradeoffs have been observed using a comparative framework of value propositions for novel nutrient recovery technologies that treat and valorize wastewater 54 . For example, for monitoring of dilute TAN waters, deployability is likely to be the primary metric due to the need to detect nitrogen discharges before they induce harmful algal blooms.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…We expect the relative importance of the core metrics of sensitivity, deployability, selectivity, and energy consumption to vary across these sensing applications. Similar tradeoffs have been observed using a comparative framework of value propositions for novel nutrient recovery technologies that treat and valorize wastewater 54 . For example, for monitoring of dilute TAN waters, deployability is likely to be the primary metric due to the need to detect nitrogen discharges before they induce harmful algal blooms.…”
Section: Resultsmentioning
confidence: 58%
“…Similar tradeoffs have been observed using a comparative framework of value propositions for novel nutrient recovery technologies that treat and valorize wastewater. 54 For example, for monitoring of dilute TAN waters, deployability is likely to be the primary metric due to the need to detect nitrogen discharges before they induce harmful algal blooms. In contrast, in-pipe monitoring at treatment plants is more likely to prioritize selectivity, especially when other constituents are present in high concentrations and could interfere with non-selective sensing mechanisms.…”
Section: Outlook For Capacitive Vetectionmentioning
confidence: 99%
“…From our experiences described here, particularly those during collaboration with a third-party laboratory, we now fully appreciate how critical it is for groups working on wastewater treatment technologies to report the correct P form in clear, specific units. Our concern that inconsistencies in P reporting are widespread is further supported by a recent systematic review of the literature on nutrient removal and recovery technologies by Kogler et al 30 In sorting reports for P removal efficiencies and effluent concentrations, three separate categories were required for reports of “TP = total phosphorus” and “PO 4 = phosphate,” and “P = general phosphorus species if species was not identified clearly.” 30 This review shows that there is a prevalent need to standardize quantitative performance metrics of nutrient removal and reuse technologies.…”
Section: Resultsmentioning
confidence: 99%
“… 2 , 14 , 27 , 28 Standardized P reporting is required to compare performance across different technologies and wastewater streams to accelerate technology adoption, yet a critical gap exists due to lack of a common set of metrics. 29 This knowledge gap in reporting metrics for P and its different chemical species is also highlighted in a recent systematic review of nutrient removal and recovery technologies by Kogler et al 30 In reviewing 292 articles across 46 sources, Kogler et al 30 found that removal efficiency and achievable effluent concentrations for P removal and recovery technologies are generally underreported, with only 16% of the articles reviewed giving adequate quantitative information for meaningful interpretation of technology performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient pollution is a consequence of the uncontrolled release of bioavailable ions containing nitrogen and phosphorus into the environment. The severe negative impacts of nutrient pollution are not only environmental [1,2], but also affect human health and the economy [3][4][5][6][7]. While agricultural runoff is the largest contributor to nutrient pollution, a growing global concern arises from inadequate on-site wastewater treatment discharges [8] which are likely underreported [9].…”
Section: Introductionmentioning
confidence: 99%